On phase, action and canonical conservation laws in kinematic-wave theory - Maugin, Gerard A. (Физика низких температур, 2008)
Canonical equations of energy and momentum are constructed in the kinematic-wave theory of waves in
a continuum. This is done in analogy with what is achieved in nonlinear continuum mechanics. The starting
point is a generalized balance of wave action. The standard formulas are recovered when the system follows
from the averaged-Lagrangian variational formulation of Whitham.